Steven-Johnson Syndrome/ Toxic Epidermal Necrolysis Overlap Complications - Novita Ifamela; Abdul Hadi Modi (Wolters Kluwer - Medknow Publications, 2024)
Steven-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) overlap is a life-threatening disorder which can lead to mortality because of systemic complications. Here, we present a case of a 22-year-old female referred to the hospital with generalized epidermal detachment and necrolysis covering approximately 25% body surface area, and unstable vital signs were found. Laboratory examination results showed acute renal failure (ARF), anemia, and hypoalbuminemia. Comprehensive treatment of skin and systemic conditions must be carried out to avoid mortality and improve the outcome. This case highlights a case of SJS overlap TEN with shock, ARF, anemia, and hypoalbuminemia safely treated by a conservative treatment strategy.